Students' Perceptions towards Blended Learning during Covid-19 Pandemic - Suripah, Suripah; Leni, Leni (Jurnal Pendidikan MIPA, 2022)
This study aims to describe students' perceptions of the application of the Blended Learning model in learning mathematics during the COVID-19 pandemic at SMK Negeri 1 Sungai Apit. This research uses descriptive quantitative research methods. The subjects of this study were 40 students from SMK Negeri 1 Sungai Apit. The object of research is students' perceptions of Blended learning during Covid 19. The research data are analysed by finding the percentage and describing students' perceptions of blended learning. Based on the results of the study showed that as many as 47% of students felt enthusiastic and liked the direct learning process because the learning methods used by teachers varied despite having limited time, 45% of students always experienced problems in accessing the learning provided by the teacher, and 46% of students dared to learn. express opinions, both face-to-face learning and online learning. Based on this research, it can be concluded that more students like Limited Face-to-face Meetings (PTMT) than online learning. Keywords: blended learning, online Learning, face-to-face, mathematics, perception. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp793-804